The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/bfj-05-2018-0291
|View full text |Cite
|
Sign up to set email alerts
|

Food-system actors’ perspectives on trust: an international comparison

Abstract: Adrienne Dockrel who contributed to data collection for Study 2 and Professor Andrew Fearne who contributed to discussions about the comparison of Study 1 and Study 2. Abstract PurposeThis international comparison study compares the perspectives of actors who contribute to trust in the food system in four high income countries which have diverse food incident histories: Australia, New Zealand (NZ), the United Kingdom (UK) and the Island of Ireland (IOI), focusing on their communication with the public, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Broadly, it was found that characteristics unique to the food incident as well as unique consumer characteristics interacted to form a trust response (an increase, decrease or no change in their trust in the food system and its actors). Briefly, consistent with previous literature (Wilson et al, 2016(Wilson et al, , 2017Tonkin et al, 2019a), food system actors' conduct during a food incident appeared to be the most critical aspect of the food incident characteristics relevant in forming the trust response. For example, Mark (pseudonyms have been used to ensure participants' anonymity) stated "Me feeling like there is openness and transparency is absolutely vital to me trusting the whole thing".…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Broadly, it was found that characteristics unique to the food incident as well as unique consumer characteristics interacted to form a trust response (an increase, decrease or no change in their trust in the food system and its actors). Briefly, consistent with previous literature (Wilson et al, 2016(Wilson et al, , 2017Tonkin et al, 2019a), food system actors' conduct during a food incident appeared to be the most critical aspect of the food incident characteristics relevant in forming the trust response. For example, Mark (pseudonyms have been used to ensure participants' anonymity) stated "Me feeling like there is openness and transparency is absolutely vital to me trusting the whole thing".…”
Section: Resultssupporting
confidence: 78%
“…Clarise: And I'm not sure if media will see itself -This investigative role was thought to include a responsibility to follow through the reporting of food incidents to resolution. These consumer perspectives of the media are both in agreement and conflict with the literature reporting media actors' own stated perspectives about their role in following up food incident stories (Tonkin et al, 2019a;Henderson et al, 2014).…”
Section: Andrew: Exactlymentioning
confidence: 70%
“…Specifically, several serious food safety incidents, cases of food fraud, and changes in food production practices have violated consumer trust across the globe [1][2][3][4][5]. While not all of these incidents have directly imposed risks to public health and safety, they do represent a breach of consumer trust and have reduced consumer confidence in the integrity of the food system [1,2,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%